COMBINED EFFECT OF COGNITIVE BEHAVIOURAL THERAPY AND RELAXED BREATHING POSTURES ON THE PEAK EXPIRATORY FLOW RATE OF ASTHMATIC SCHOOL CHILDREN - Dr. Gladies Kamalam S.,; Dr. Santheep S,; Dr. Vel Murugan G.,; Dr. Manivannan S.,; Dr. Dinesh Dharmalingam, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2025)
Asthma, a chronic respiratory condition prevalent in school-aged children, is exacerbated by psychological stress, impairing pulmonary function and quality of life (QOL). This single-group pre-post intervention study evaluated the synergistic impact of Cognitive Behavioural Therapy (CBT) and relaxed breathing postures on Peak Expiratory Flow Rate (PEFR) in 20 asthmatic children (8–14 years). Over 12 weeks, participants received biweekly CBT sessions and daily breathing exercises (diaphragmatic and alternate nostril breathing) alongside standard care. Post-intervention, significant improvements were observed in PEFR (mean difference: 43.016 L/min, p < 0.05) and Pediatric Asthma Quality of Life Questionnaire (PAQLQ) scores (t = 2.191, p < 0.05). Anxiety levels and asthma-related symptoms decreased, underscoring the intervention’s dual psychological and physiological efficacy. These findings advocate integrating non- pharmacological strategies into pediatric asthma management to reduce medication dependence and enhance holistic well- being.